PELAKSANAAN FUNGSI PEMERINTAHAN OLEH PEMERINTAH KABUPATEN KEPULAUAN MERANTI DALAM PENGEMBANGAN KOPI LIBERIKA DI DESA KEDABURAPAT TAHUN 2020-2022 - Prastama, Leonardo Ayi; ', Adlin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
This study aims to determine the implementation of the functions of the Meranti Islands Regency government in developing Liberika coffee in Kedaburapat Village and the factors that become obstacles in implementing this function. The theory used in this study is the theory of government functions according to Ryas Rasyd. The type of research used is qualitative with a descriptive approach. Data were collected by the authors using interview and documentation techniques. The data used are primary data and secondary data. The results of the study show that the government function in the development of Liberika coffee in Kedaburapat Village is carried out using 4 functions, namely the service function, the regulatory function, the development function and the empowerment function. The service function is carried out by preparing a service forum for the community with the Agricultural Service Unit (UPP) office to respond to complaints or requests from the community in agricultural management, especially for Liberal coffee farmers. The regulatory function carried out by the government in carrying out government functions is to determine the selling price of coffee fruit, but this has not yet been realized. The development function carried out by the government cannot be said to be successful, because the road access to and from Kedaburapat Village cannot be said to be good and proper. The empowerment function carried out by the government is to carry out education and counseling for Liberika coffee farmers, provide financing and capital facilities, and strengthen farmer institutions. All of this has been carried out quite well, although there are still deficiencies in several matters such as capital, and others. The factor that hinders the development of liberika coffee farmers is the lack of knowledge of the farming community both in technology and coffee maintenance techniques. This resulted in them only using traditional farming methods, so that their production results were not too optimal. Keywords: Government Functions, Government Functions, Liberika Coffee Farmers, Kedaburapat Village